Mixed cation perovskite solar cells by stack-sequence chemical vapor deposition with self-passivation and gradient absorption layer. (June 2018) - Tong, Guoqing; Li, Huan; Li, Guopeng; Zhang, Ting; Li, Chengdong; Yu, Linwei; Xu, Jun; Jiang, Yang; Shi, Yi; Chen, Kunji
Abstract: Mixed cation halide perovskite solar cells (PSCs), in a formula of ABX3 where A is a mixture of formamidinium (FA) or cesium (Cs) cations, represent a promising new architecture to achieve largely improved stability and higher power conversion efficiency (PCE). While all these mixed-cation PSCs were synthesized via a solution method, we here propose and demonstrate a precisely tunable stack sequence physical-chemical vapor deposition (SS-PCVD) approach to prepare a mixed-cation absorber in CsBr-doped hybrid organic perovskite, which features a beneficial gradient bandgap profile to enable an improvement of PCE from 11.69% in pure FAPbI3 to 18.22% in mixed-cation PSCs. Remarkably, an excellent stability in ambient exposure for 60 days has been achieved by a proper control of the CsBr cation incorporation and interface passivation. This new approach indicates a simple, precisely tunable and low cost fabrication strategy to implement high performance and scalable mixed-cation halide perovskite solar cells. Graphical abstract: fx1 Highlights: A new stack-sequence physical-chemical vapor deposition to achieve a gradient Cs-doping and bandgap profile shows a high power conversion efficiency of 18.22%. An excellent stability in ambient exposure for 60 days has been achieved by a proper control of the CsBr cation incorporation and interface passivation. Indicating a simple, precisely tunable and low cost fabrication strategy to implement high performance and scalable mixed-cation halide perovskite solar cells.